Analisis Gaya Bahasa Pada Karya Puisi Siswa Kelas 10 SMA Negeri 1 Talamau - Faulia Rahmah, Elsi; Marta, Tri Annisa; Hanif, Ahmad; Putri, Atika Aprilia; Nasution, Rolan Rizki; Afnita, Afnita (Universitas Pakuan, 2025)
ANALYSIS OF LANGUAGE STYLE IN THE POETRY WORKS OF 10TH-GRADE STUDENTS OF SMA NEGERI 1 TALAMAUThis study aims to analyze and describe the figures of speech used in the poetry of 10th-grade novice students at SMA Negeri 1 Talamau. The subjects were selected based on their characteristics as beginner writers who are just starting to develop their creative writing skills, especially in poetry. The data consists of all diction containing figures of speech in a collection of poems written by the students. A qualitative descriptive method with content analysis techniques was used. The findings show that 10th-grade students are capable of using a variety of figures of speech in their poems, though with different frequencies and variations. The dominant figures of speech were those of comparison, specifically personification and metaphor, which reflect the students' attempts to animate inanimate objects and provide implicit depth of meaning. The study also found the use of figures of opposition like hyperbole and figures of repetition such as anaphora, albeit in smaller numbers.The use of these stylistic elements by novice students demonstrates a level of understanding and mastery of stylistics in poetry, despite some figures of speech being rarely or never used. The implication of this research is the need for more intensive development of learning materials and teaching strategies to enrich the variety of language styles used by students, thereby improving the quality and expressiveness of their poetry in the future.